Methylenetetrahydrofolate reductase C677T polymorphism is associated with estimated glomerular filtration rate in hypertensive Chinese males - Dong Qing; Tang Genfu; He Mingli; Cai Yunqing; Cai Yefeng; Xing Houxun; Sun Liming; Li Jianping; Zhang Yan; Fan Fangfang; Wang Binyan; Sun Ningling; et al. (BMC Medical Genetics, 2012)
Abstract Background Plasma level of total homocysteine (tHcy) is negatively correlated with kidney function in general population. However, the causal mechanism of this correlation is poorly understood. The purpose of this study is to investigate the association of methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism, which is a major genetic determinant of the plasma tHcy level, with estimated glomerular filtration rate (eGFR) in Chinese. Methods A total of 18 814 hypertensive patients (6 914 males, 11 900 females) were included in the study. Results Association between the eGFR and MTHFR C677T genotype was examined by sex-specific regression analyses. In males, TT genotype was associated with 1.37 ml/min/1.73 m2 decrease in eGFR (p = 0.004) and with an increased risk (OR = 1.32, p = 0.008) for the lowest quintile of eGFR after adjusting for age, BMI, and blood pressures. However, such association was not observed in females (p > 0.05). This association suggests MTHFR C677T polymorphism may play a role in the regulation of eGFR in males. Conclusions MTHFR 677 T is a risk allele for decreased kidney function in Chinese males, implicating this gene in the pathogenesis of chronic kidney disease (CKD).